Non Penal Policy for Preventing Terorism Criminal Acts Through Contextualization Jihad Command in Islamic Sharia: Kebijakan Non Penal Pencegahan Tindak Pidana Terorisme Melalui Kontekstualisasi Perintah Jihad dalam Syariat Islam - Errix Dwi Saputra; Indah Sri Utari (Universitas Negeri Semarang, 2025)
This research is a research in the field of criminal law with a study of non-penal policies regarding the prevention of criminal acts of terrorism, the purpose of this study is to determine the factors that cause perpetrators of criminal acts of terrorism to interpret their actions as jihad and what form of policy can be taken to prevent criminal acts of terrorism. The type of research used here is a normative research type with a conceptual approach, namely comparing the events of criminal acts of terrorism in the name of jihad with the concept of jihad in Islamic law. It is hoped that this research can contribute to criminal law both in terms of legal culture, legal structure and legal subtance in order to understand that Islam is a just religion and all incidents of criminal acts of terrorism are a form of deviation from Jihad.